2014
DOI: 10.1590/s1517-70762014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Análise do potencial pozolânico da cinza de casca de arroz (CCA) através da técnica de Refinamento de Rietveld

Abstract: É um consenso que a cinza de casca de arroz é um resíduo agrícola com comprovada eficiência pozolânica. Contudo, por se tratar de um resíduo, apresenta problemas de variabilidade decorrente dentre outras coisas de sua origem e dos diferentes processos de geração, fator este que dificulta sua comercialização. Hoje em dia, a determinação da atividade pozolânica do resíduo e determinada pela NBR 5752[3] (ABNT, 2012) e NBR 5751(2) (ABNT, 2012). A desvantagem com relação a estes ensaios é o tempo que se leva para t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
1
3
0
4
Order By: Relevance
“…2b) also had characteristics of an amorphous material, due to the presence of a halo between 15º and 40° (2θ). The characteristic crystalline peaks of cristobalite (SiO 2 ), a form of free silica (together with quartz and tridymite), were observed, similar to that found by Cordeiro et al [28], who reported that its presence is an indication that the burning of the RHA was carried out at a high temperature (~950 °C) for a prolonged combustion time. It should be noted, in this regard, that the burning temperature and time are important factors that define the content of amorphous silica or crystalline phases present in the RHA.…”
Section: Fly Ash and Rha Characterizationssupporting
confidence: 84%
“…2b) also had characteristics of an amorphous material, due to the presence of a halo between 15º and 40° (2θ). The characteristic crystalline peaks of cristobalite (SiO 2 ), a form of free silica (together with quartz and tridymite), were observed, similar to that found by Cordeiro et al [28], who reported that its presence is an indication that the burning of the RHA was carried out at a high temperature (~950 °C) for a prolonged combustion time. It should be noted, in this regard, that the burning temperature and time are important factors that define the content of amorphous silica or crystalline phases present in the RHA.…”
Section: Fly Ash and Rha Characterizationssupporting
confidence: 84%
“…Among its characteristics, the most notable are high melting point, high porosity and specific surface, high reactivity during structure changes, low iron percentage, and the chemical reactions of silica. 27 Silica represents an average value of 95% in the constitution of the elements of the RHA. 28 According to Singh and Chauhan, 29 waste obtained from agricultural sources, such as rice husk ash, is becoming the focus of research due to its use as reinforcing components in metal matrices.…”
Section: Reinforcing Materials For Aluminum-based Alloymentioning
confidence: 99%
“…Temperature is known to have a strong influence on the production of glass foams [ 11 , 19 ]. They can be produced at 800–950 °C [ 20 , 21 ] with a low heating rate, which can influence the formation of pores [ 22 ]. Therefore, glass foams are widely used in civil construction as blocks in the insulation of ceilings and walls for both high and low temperatures, as sub-grade improvement material, or as light aggregates in concrete [ 12 , 17 , 23 ].…”
Section: Introductionmentioning
confidence: 99%